Parâmetros de estresse oxidativo em cães naturalmente infectados pelo vírus da cinomose - Curtis, Andressa Oliveira de (2013)
Canine distemper disease is a severe multisystem disease that affects the respiratory, hemolymphatic, gastrointestinal and neurological systems. The lesions induced by replication of canine distemper virus (CDV) produce an increase in reactive oxygen species (ROS), leading to oxidative stress. The aim of this study was to investigate parameters of oxidative stress by measuring the lipid peroxidation through the thiobarbituric acid reactive substances (TBARS) and the activity of the enzymes catalase (CAT) and superoxide dismutase (SOD) in dogs naturally infected with distemper virus. In this study we used 33 animals positive for CDV, attended at the Veterinary Hospital of the University of Rio Grande do Sul (UFRGS) and 21 clinically healthy animals were used as control. For the confirmation of the diagnosis RT-PCR (Reverse Transcription Polymerase Chain Reaction) was performed in samples of rectal swab and/or serum. This study demonstrated a significant difference in lipid peroxidation, SOD and CAT activities in the analyzed groups, suggesting the involvement of oxidative stress in the pathogenesis of the disease.